A cross-sectional study on patient satisfaction at International Islamic University Malaysia (IIUM) Family Health Clinic, Kuantan Pahang Malaysia - Che' Man, Mohamad; Yusof, Muhammad Zubir; J, Amsyareezmi; A, Amira Sofiyah; K, Fakhri Syahmi (ScienceForecast Publications, 2019)
Introduction: Patient satisfaction may be defined as a representation of attitude, emotion and perception towards health services provided. It may be measured using tools such as patient satisfaction surveys thereby allowing healthcare provider to improve their quality of service. Thus, our study aims to measure the level of patient satisfaction towards International Islamic University Malaysia (IIUM) Family Health Clinic, Kuantan, Pahang. Objectives: To measure the level of patient satisfaction towards the primary care service of International Islamic University Malaysia (IIUM) Family Health Clinic, Kuantan, Pahang, Malaysia. Methodology: A cross-sectional study was conducted among 200 patients attending IIUM Family Health Clinic selected through convenient sampling. A set of self-administered validated questionnaire which includes the Patient Satisfaction Questionnaire 18 (PSQ-18) were given to the respondents. Descriptive analysis was used to describe socio-demographic and socioeconomic factors of respondents as well as the score of patient satisfaction. Relation between sociodemographic and patient satisfaction were analyzed using Kruskal Wallis test. Results: Out of majority of the respondents were from the age group 30 to 49 years-old (57.7%), female (63.9%), Malay (96.4%) Muslim (98.5%), live in urban residence (84.0%), married (68.0%), have tertiary level education (87.6%). working (67.0%), and have a household income of more than RM3000. The overall satisfaction score was 70.75 (78.6%). Highest satisfaction was in interpersonal manner, and the lowest was in time spent with doctors. There were significant association between overall satisfaction with marital status, general satisfaction with education background, interpersonal manner with ethnic and marital status, financial aspect with age group, working status and marital status, and time spent with doctor with age group of patients. Conclusion: Mean score and percentage of the patient satisfaction was high in IIUM Family Health Clinic. However, there are areas that are still concerning and require improvement such as the time spent with doctor. By doing so, the quality of care and overall patient satisfaction may be improved.